Tanzania : Statistical Annex. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
This Statistical Annex discusses the economic indicators of Tanzania for the period 1990-99. The annexure includes gross domestic product and expenditure; production and outcome of food crops and manufactured commodities; gross capital formation by public and private sectors; analysis of savings-investment relationship; producer prices for selected food and export crops; indices and composition of exports and imports; balance of payments; budgetary transfer payments; central government debt and debt-service payments; summary accounts of the Bank of Tanzania; summary accounts of domestic money banks; and so on.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet